Theatre Royal, Drury-Lane, the last night, Friday, April 6, 1827, grand performance of Antient & Modern music - Theatre Royal, Drury Lane (London, England):::Creator:::::::::::: (Theatre Royal ; printed by W. Reynolds; London, 2020)
Handbill listing works to be performed at the Theatre Royal, Drury Lane, London, on April 6, 1827, including selections from Beethoven's Fidelio and Handel's Acis and Galatea, with names of performers.